The Process of Promoting the Economic base of the Thai Lanna Textile Handicraft Community in Sukhothai (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to study the potential and develop skills in textile handicrafts of Thai Lanna ethnic group inSukhothai Province. The research process was carried out as follows: 1) study the community context, 2) community-basedknowledge transfer, and 3) the development of textile products using quantitative and qualitative research methods. Researchtools include interviews and questionnaires, collected data from group conversations, and the satisfaction was assessed by aspecific sampling group from key informants from Thai Chanasuek Sub-District Community, Thung Saliam District, Sukhothaiprovince, in the group of 30 people by analyzing descriptive statistics. Research results showed that 1) the Thai Lanna ethniccommunity is a community that immigrated from Lampang Province with the traditions, culture, language, traditions andweaving with a flower pattern which has been the identity of the community and has been produced as costumes, blankets andbags. 2) The knowledge of the weaving production of the community arises from the dynamic exchange of knowledge betweenthe conveyer and the recipient of knowledge in the form of explicit knowledge. Knowledge consolidation and the conversion ofknowledge were applied to enhance the textile products and the economic base of Thai Chanasuek Sub-District Community. 3)Woven fabric pattern design, using the concept of Neem flower to develop the pattern by using cotton brocade technique andprocessing of woven fabrics into clothing with satisfaction in utility, shape and beauty. The average was at a very good level